Demographic transition and political stability: Does corruption matter? - Mohammad Reza Farzanegan; Stefan Witthuhn (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
A demographic transition resulting from an increase in the size of the young working age population can be a blessing or a curse for economic performance. We focus on the political stability effects of a larger youth population and hypothesize that corruption matters in this nexus. Using panel data covering the period of 2002-2012 for more than 150 countries, we find a negative interaction effect between the relative size of the youth population (17-25 years old) within the total working age population (15-64 years old) and corruption on political stability. This finding is robust, controlling for country and time fixed effects and a set of control variables that may affect stability. The negative interaction term between corruption and the youth population remains robust when we control for the persistency of political stability and the possible endogeneity of the main variables of interest through dynamic panel data estimations. Our findings shed more light on the political turmoil in the Arab world, with the so-called Arab Spring.
Keywords: D73; D74; E02; H56; J11; 330; demographic transition; youth population; political stability; corruption